Household resilience and coping strategies to food insecurity: An empirical analysis from Tajikistan [in Tajik] - Rajiv, Sharanya; Aliev, Jovidon (International Food Policy Research Institute, 2024)
Resilience Index Measurement Analysis (RIMA) is applied to panel household survey data from 2007, 2009, and 2011 in Tajikistan to investigate the causal impact of household resilience on food security in the presence of coping strategies. Key findings • Three significant factors define household resilience capacity: access to basic services, including affordable energy supply; assets; and social safety nets. The latter two factors underscore the importance of formal and informal transfers as effective responses when shocks intensify. • Coping strategies allow households to quickly adjust their behavior to adapt to shocks in the short-term, potentially enhancing their overall resilience in the long-term. • Resilience capacity at a given point in time enhances households’ future food security. Households with higher resilience capacity are likely to have a higher household food expenditure share (HFES) and less likely to face loss of food expenditure share, particularly due to the protective effect of resilience when shocks intensify. • While households with an older head have higher food expenditure share, households with a male head and/or located in rural areas are less likely to face a worsening household food expenditure share. • As household size increases, the household food expenditure share initially decreases but eventually increases at a gradual pace. Conversely, as size increases, households are initially less likely to experience loss of HFES, but this likelihood eventually increases.